Factors affecting liquidity in Vietnam’s commercial banks - Vu, Cẩm Nhung; Nguyen, Thị Thẩm; Nguyen , Xuân Hoàng Tuấn; Bui, Thị Nhi (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
The paper analyzes and determines the factors affecting liquidity in 24 commercial banks in Vietnam from 2010 to 2022. The study uses regression models OLS, FEM, REM and overcomes the model. GLS model through STATA 17 software to test and overcome defects, in which the study uses 12 variables and experimental results show that there are 8 factors affecting liquidity of commercial banks including: 1) Bank size, (2) Profit ratio, (3) Total short-term debt/equity ratio, (4) Loan balance/total customer deposit ratio, (5) Capital ratio owner/total assets, (6) Bad debt ratio, (7) Inflation rate, (8) Marginal interest income ratio. From there, draw conclusions and propose some policy implications to help commercial banks develop and ensure liquidity effectively.